Movie translation: types and features (Journal of Oriental Studies, 2018)
The article discusses the role and importance of kinoperevoda in modernsociety, as well as the relevance of kinoperevoda research in Kazakhstan.Now the Kazakh film industry is dominated by translation of foreign,particularly Western and Asian movies. This process directly affects thedevelopment of kinoperevoda. In this regard, it is important to raise questionskinoperevoda. This article describes the types of kinoperevoda anduse in Kazakhstan kinoperevode.